Sleep and Obesity in Children and Adolescents - Hart, Chantelle N. (2011)
The purpose of the present review is to provide a comprehensive update of current epidemiological studies that have assessed the association between sleep and obesity risk. Data from 29 studies conducted in 16 countries suggest that short sleep is associated with an increased risk for being or becoming overweight/obese or having increased body fat. Late bedtimes were also found to be a risk factor for overweight/obesity. Findings also suggest that changes in eating pathways may lead to increased body fat. Future experimental studies are needed to enhance our understanding of the underlying mechanisms through which sleep may play a role in the development and maintenance of childhood obesity.